Argumentative competences development in online discussions forums - Guzmán-Cedillo, Yunuen I.; Flores-Macías, Rosa-del-Carmen; Tirado-Segura, Felipe (Anales de Psicología / Annals of Psychology, 2013)
Setting out an analysis and definition of argumentative competence from a constructive perspective is the objective in this paper. Furthermore it proposes online forums which promote debate as an appropriate environment to develop this kind of competences. Argumentative competence concept suggested here comes from an analysis of different documents and researches about critical thinking, argumentation, competences and online forums. This concept involves at list twelve elements to group into three competences components (knowledge, skills and attitudes) to deploy in dialogic arguments that develops a critical thinking in an individual and group cognitive engagement where the topic and instructional design are fundamental.